Prospective study at public universities to 2040 - Chung Pinzás, Alfonso Ramón (2013)
This paper shows, in a general way, the results of the prospective study to the public universities to 2040. To make this analisys it designed and applied the Multi–Scenario Method; which is useful to make studies when the experts cannot be gathered to apply the prospective tools. This method is explained in order to be applied in similars studies.